The Routledge international handbook of valuation and society - Krüger, Anne (Routledge, Taylor & Francis Group, 2025)
The Routledge International Handbook of Valuation and Society builds on the growing research interest in practices of valuation throughout contemporary society, providing an up-to-date overview of the different facets of research in the sociology of valuation.The handbook is divided into five major sections with attention to the treatment of valuation in major areas of sociological theory, as well as its key concepts, discourses, and approaches:Part I: Theoretical perspectivesPart II: Central valuation practices in societal spheresPart III: Cross-cutting valuation practicesPart IV: Valuation and societal changePart V: ReflectionsTogether, the chapters in this book characterize distinctive practices of valuation across different societal spheres, such as education and science, arts and culture, economic life, the environment or digital culture and social media. They also examine the role of valuation in contemporary society and consider the ways it effects social change.This seminal handbook aims at taking stock of the development of the study of valuation with a selection of topics that are important for understanding core perspectives and developments as well as anticipating its future orientation. It will appeal to scholars across the social sciences with interest in the ubiquity of the valuation practices and its effects on social life
Introduction ; Part I: Theoretical perspectives ; 1. Classifications, the sacred, and moral individualism: Durkheimian perspectives on valuation; 2. Anthropological perspectives on value and valuation; 3. The rise of a French pragmatic sociology of values; 4. On Science and Technology Studies and valuation; 5. Relinquishing value: Aristotle and the substances of institutional practice; 6. Value(s) and (e)valuation in sociological systems theories; 7. The ‘new’ sociology of knowledge and the sociology of valuation; Part II: Central valuation practices in societal spheres ; II. A. Economic valuation ; 8. Economic valuation; 9. Where the value is: Accounting and the spatialization of worth ; 10. Rethinking value through waste: About devaluation and society; II. B. Valuation in education and science ; 11. The panopticon of evaluation in educational organizations; 12. Research on research evaluation: From particularism to synthesis ; 13.
- Competition and valuation in science and higher education; 14. How evaluations fail: Investigating scientific misconduct; II. C. Valuation in arts and culture ; 15. Valuation practices in the visual arts; 16. What is good music? Distinction and valuation in music worlds; 17. What makes a book "good"? New perspectives on literary evaluation; Part III: Cross-cutting valuation practices ; III. A. Valuation of human beings ; 18. Self-optimization; 19. (A) Being worth it? Self-worth and self-(e)valuation within Valuation Studies ; 20. Social inequality: A neglected topic in studies of valuation and evaluation? ; III. B. Digital valuation ; 21. Algorithms and valuation: In search of a means to get beyond opacity ; 22. Digital surveillance and valuation in datafied societies ; 23. Valuation and digital platforms; 24. The social logics of platform units: A brief history of valuation practices online; Part IV: Valuation and societal change ; 25.
- Economization: Valuation and the boundaries of valuation games; 26. Risky values: Seeing risk through the lens of Valuation Studies; 27. Valuation and sustainability; 28. Datafied and (e)valuated: Datafication as driver of contingent (e)valuation ; 29. The amateurization of valuation in the digital age; 30. Worlds of rankings research; Part V: Reflections ; 31. Reflections on the emergence of a research field: An interview with Michèle Lamont; Index
Keywords: bicssc / Social theory; bicssc / Higher & further education, tertiary education; bicssc / Research methods - general; bicssc / Humanities